Between Education and Science: Which is Closer to Doctoral Education? - Mkhitaryan, Atom («Ալվարդ Օհանջանյան Վառլենի»)
With “Berlin Communiqué”, the Bologna Process began to focus on doctoral education as the third level of higher education [1]. Since then, many improvements and concretisations have been made at the European level. The traditional doctoral education - Aspirantura in Armenia (and in other Soviet republics) was a model of “apprenticeship”: the responsibility for the PhD student is exclusively a matter of the supervising professor (or “scientific supervisor”) due to the close relation between the doctoral candidate and professor. Then, after Armenia’s independence, structured postgraduate programs gradually began to increase. This process proceeded at almost the same speed in other European countries that joined the Bologna Process (Armenia joined the Bologna Process in 2005). Բեռլինյան կոմյունիկեով Բոլոնիայի գործընթացը սկսեց կենտրոնանալ դոկտորական կրթության վրա՝ որպես երրորդ մակարդակի բարձրագույն կրթություն [1]: Այդ ժամանակից ի վեր եվրոպական մակարդակով բազմաթիվ բարելավումներ ու կոնկրետացումներ են կատարվել։ Ավանդական դոկտորական կրթությունը` ասպիրանտուրան Հայաստանում (և խորհրդային այլ հանրապետություններում) «աշկերտության» մոդել էր. ասպիրանտի պատասխանատվությունը բացառապես գիտնական պրոֆեսորի (կամ «գիտական ղեկավարի») խնդիրն է՝ ասպիրանտի և պրոֆեսորի սերտ հարաբերություններով պայմանավորված: Այնուհետեւ, Հայաստանի անկախացումից հետո աստիճանաբար սկսեցին աճել կառուցվածքային երրոդ մակարդակի կրթության ծրագրերը։ Այս գործընթացը գրեթե նույն արագությամբ ընթացավ Բոլոնիայի գործընթացին միացած եվրոպական այլ երկրներում (Հայաստանը միացավ Բոլոնիայի գործընթացին 2005թ.): С «Берлинским коммюнике» Болонский процесс начал фокусироваться на докторантуре как на третьем уровне высшего образования [1]. С тех пор на европейском уровне было сделано много улучшений и конкретизаций. Традиционное докторантское образование — аспирантура в Армении (и в других советских республиках) было моделью «ученичества»: ответственность за аспиранта — это исключительно дело курирующего профессора (или «научного руководителя») из-за тесной связи между докторантом и профессором. Затем, после обретения Арменией независимости, структурированные программы аспирантуры постепенно начали расширяться. Этот процесс шел почти с той же скоростью в других европейских странах, присоединившихся к Болонскому процессу (Армения присоединилась к Болонскому процессу в 2005 году).
Keywords: Educational Management